Pupil’s mental models of earth internal structure - Torres, Joana (2020)
Mental models are fundamental for understanding the construction of knowledge and people’ actions, constituting an important area in science education. In fact, Johnson-Laird (1983) argued that people think and reason with mental models, as it is impossible to directly understand the world. For this author, human mind construct internal representations, which are considered a bridge that connects people with the world. Mental models represent objects or specific situations, capturing its essential characteristics. Although mental models are considered to be personal, incomplete, unstable and unscientific they allow pupils to understand and explain phenomena. As so, according to their experiences, pupils construct their own mental models, which are useful for their daily life. On the other hand, conceptual models are considered to be precise representations coherent with scientific knowledge that are introduced to them in the classroom. When pupils are confronted with conceptual models which are frequently different from their own mental models, restructuring processes may occur in diverse ways. Consequently, it is important that teachers become aware of the difficulty of this process and recognize the relevance of the diversity of their pupils’ mental models, in order to promote activities that allow them to construct their models in an effective way. Pupils should have the opportunity to evaluate the importance of conceptual models and to correctly compare them with their previous knowledge. The present study aims to analyze how primary pupils imagine and represent the internal structure of the Earth. To attain this purpose, a questionnaire was constructed and validated by two university experts in primary education. The questionnaire asked pupils to draw the Earth’s interior and to write an explanation of their own drawing intending to get an approximation of their Earth’s internal structure mental models. One hundred and seventeen pupils of the last year of the primary school participated in this study. The sample had 58,1% of boys and 41,9% of girls, with ages ranging from 9 to 11 years old. The collected data was analyzed and mental models were classified into different categories: (i) Real Concentric Layers Model; (ii) Unreal Concentric Layers Model; (iii) Simple Random Structure Model; (iv) Complex Random Structure Model; (v) Fictional Model; (vi) Mixed Model; and (vii) External Model. Complex Random Structure Model was the model represented by the majority of pupils. In fact, only 35,9% of participants represent the Earth’s internal structure divided into layers. Although pupils were allowed to represent movement with arrows, most of them possess a static mental model of the Earth.